Impacto de la atención farmacéutica en los resultados clínicos y en la calidad de vida de pacientes con diabetes mellitus tipo 2 - Maidana, G. M.; Mastroianni, P. C. [UNESP]; Vera, Z.; Samaniego, L.; Acosta, P.; Lugo, G. B. (My University, 2016)
Introduction: The relationship between quality of life and health combines elements intrinsic of the individual as well as external ones that interact with him. They possess the ability of changing the state of health. It includes such areas as physical, somatic, psychological and social. Objective: To evaluate the clinical parameters and quality of life of patients with Type 2 Diabetes Mellitus, within a program of Pharmaceutical Care. Methodology: Randomized Clinical Trial with measurement of variables before and after the evaluation. Non probabilistic. Convenience. 32 patients participated in the intervention group; 32 in the control group. Monthly interviews were conducted for 6 months, from October 2011 to June 2012. Results: The average age of the patients was 55,6±10,6 years. They were mostly women. The evolution of the condition was 8,96±8,13 years. The most frequent associated pathology was high blood pressure in 82% of them. The glycemia levels of the patients improved 35%, where 24 of the patients showed an index. 130 mg/dL; glycosylated hemoglobin level improved 22%, where 15 patients achieved desired parameters (≤ 6,5%). The quality of life of the intervened group improved from 56.3 % to 71.3% in all dimensions showing a decrease in body pain for the intervened group. Body pain levels for the control group decreased from 57.4 to 46.1 % showing an increase in the body pain dimension. Conclusion: Clinical parameters and quality of life of diabetic patients is positively influenced by the intervention of the pharmacist in pharmaceutical care.
Impact of pharmaceutical care in clinical outcomes and quality of life of patients with type 2 diabetes mellitus
Keywords: Pharmaceutical assistance; Quality of life; Type II diabetes mellitus